PAULBRONNIMANNINAE RETTORI & ZANINETTI, 1993 (FORAMINIFERIDA, AMMODISCIDAE) AND OTHER ANISIAN FORAMINIFERS FROM THE PIZ DA PERES SECTION (VALDAORA-OLANG, PUSTERIA VALLEY, DOLOMITES, NE ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
The anisian  succession exposed in the Piz da Peres area, studied by De Zanche et al. (1992) using sequence  stratigraphy, is here examined from a micropaleontological  point of view. The Recoaro Limestone, deposited during highstand  time, contains the most diversified microfauna of the stratigraphic succession; it is Pelsonian in age, with the rypical association Meandrospira dinarica-Pilammina densa; the coeval Pelsonian foraminifers Paulbronnimannia  judicariensis  (Premoli Silva, 1971) and Paulbronnimannia  whittakeri Rettori gen. n., sp. n,, are also  present.
Keywords: Foraminifers; Middle Triassic; Pelsonian; New Genus; New species; Biostratigraphy; Sequence stratigraphy.